Effect of bonding time on the interfacial microstructure and mechanical properties of diffusion bonded tungsten alloy/steel joints using CrFeCoNiCu high entropy alloy interlayer - Shangru Meng; Mengxiang Zhang; Yifan Han; Wensheng Liu; Yunzhu Ma; Qingshan Cai (Journal of Materials Research and Technology)
In this paper, the microstructure and properties evolution of 93W-4.9Ni-2.1Fe alloy (93W, wt.%) and 30CrMnSiNi2A steel (wt.%) under different bonding times were studied with CrFeCoNiCu high entropy alloy (HEA) as the interlayer. The results show that a -Fe7W6 intermetallic compound layer is found in the diffusion zone between W particles and HEA at the 93W/HEA interface. The growth behavior and mechanism of μ layer were discussed. At the HEA/steel interface, rod-like Cr7C3 phase and nanoparticle Cr23C6 phase are formed in HEA due to the diffusion of C, which gradually coarsened and their content increased with the extension of bonding time. The tensile test shows that the maximum tensile strength of the joint reaches 592 MPa when the joint is kept at 950 °C for 1 h. The joint failure mode is the mixed fracture of μ phase, W particle and FCC solid solution.